Diversity resistance in organizations - Thomas, Kecia M. (Foreword, 2008)
This is a groundbreaking volume that provides informed, balanced yet frank discussion of US workplace diversity and diversity resistance issues. The chapters in this book put a name on behaviors and practices that have existed in the workplace for a long time, yet until recently have had no name. Further, the majority of the chapters innovatively link existing psychological and organizational factors such as fear, uncertainty, power, emotions, and organizational change and development. The book's editors and authors emphasize that we need to know more about diversity resistance, both in overt and covert forms. To guide us, we can draw on existing research and practice literature that have both theoretical and empirical depth. This timely volume's first chapter deconstructs the growing prevalence of hangmen's nooses as a manifestation of resistance to diversity that is visibly overt, hostile, and interpersonal. The authors also shed light on how nooses surprisingly exemplify diversity resistance that is also frequently covert, subtle, and frequently silent. The book is appropriate for undergraduate and graduate students in industrial and organizational psychology, human resources management, diversity management, sociology of work, organizational change, and cultural diversity within organizations. It provides a central resource for classes on prejudice and discrimination in organizations, emotions at work, personnel psychology, strategic human resources management and cultural issues in human resources management. Professionals and practitioners who increasingly interact with diverse employees will find this book essential to their work.